The impact of fiscal policy on profits - Margarita Katsimi; Vassilis Sarantides (Center for Economic Studies and ifo Institute (CESifo), 2009)
This paper investigates the impact of fiscal policy on profits using panel data for 19 high-income OECD countries during the period 1975-1999. We estimate a profit equation in which profits depend on a set of fiscal variables. Our empirical method is based on a consistent treatment of the government budget constraint, and we try to disentangle the effects of different spending and taxation items. As far as public spending is concerned, our results strongly suggest that capital expenditures are associated with higher profits, while expenditures on wages and salaries deteriorate profits. At the same time our results indicate that transport and communication expenditures increase profits, while the opposite holds for defense expenditures. On the revenue side, both direct and indirect taxation tend to decrease profits. However, a more detailed sub-division of direct taxation indicates that social security contributions have a neutral effect on profits.
Keywords: E62; H32; H54; 330; fiscal policy; profits; quality of public expenditure; Finanzpolitik; Öffentliche Ausgaben; Steuerpolitik; Wirkungsanalyse; Gewinn; OECD-Staaten